Genetic differences for nitrogen uptake and nitrogen use efficiency in some Azerbijani bread wheat landraces (TRITICUM AESTIVUM L.) - Gholamreza Khalilzadeh; Ebrahim Azizov; Alireza Eivazi (Global Journal of Food and Agribusiness Management, 2020)
Genotypic differences in major components of the nitrogen uptake and use efficiency between bread wheat (TRITICUM AESTIVUM L.) landraces was evaluated in field conditions under varied N fertilization levels (0, 200 kg N ha-1 ) based on RCB design with three replications. All characters showed significant genotypic diffrences. Results showed that high variation between genotypes in almost trials by reducing nitrogen. The interaction of G × N for all characters was significant, except harvest index (HI). The highest grain yields belong to Girmizigul, Bc-5, Bc-7 and Bc-17 and the lowest sensibility to N reduction belong to Bc-13 and Bc-14. Landraces of Bc-12, Bc-14 and Bc-16 for grain N concentration and Bc-4, Bc-7 and Bc-14 for straw N concentration showed the lowest reaction to N reduction. Among of N use efficiency components, Nitrogen uptake efficiency was contribution for about 95% of variation at both levels of N. The best landraces for N uptake efficiency were Bc-5, Bc-11 and Bc-15. Grain yield at all N0, N+ and G×N interaction was the best explained by the Grain N concentration than grain N yield. Results indicated that both nitrogen uptake efficiency and grain yield had been more importance criteria for selection of high N use efficiency of wheat landraces in a breeding program. In this experiment, landraces Bc-5, Bc-11 and Bc-15 were the best genotypes with high yield potential and N Uptake.